Cerebral Microcirculation and Histological Mapping After Severe Head Injury: A Contusion and Acceleration Experimental Model - Bellapart, Judith; Cuthbertson, Kylie; Dunster, Kimble; Diab, Sara; Platts, David G.; Raffel, Owen Christopher; Gabrielian, Levon; Barnett, Adrian; Paratz, Jenifer; Boots, Rob; Fraser, John F. (Frontiers in Neurology, 2018)
Background: Cerebral microcirculation after severe head injury is heterogeneous and temporally variable. Microcirculation is dependent upon the severity of injury and it is unclear how histology relates to cerebral regional blood flow. Objective: This study assesses the changes of cerebral microcirculation blood flow over time after an experimental brain injury model in sheep and contrasts these findings with the histological analysis of the same regions with the aim of mapping cerebral flow and tissue changes after injury. Methods: Microcirculation was quantified using flow cytometry of color microspheres injected under intracardiac ultrasound to ensure systemic and homogeneous distribution. Histological analysis used amyloid precursor protein staining as a marker of axonal injury. A mapping of microcirculation and axonal staining was performed using adjacent layers of tissue from the same anatomical area, allowing flow and tissue data to be available from the same anatomical region. A mixed effect regression model assessed microcirculation during four hours after injury and those results were then contrasted to the amyloid staining qualitative score. Results: Microcirculation values for each subject and tissue region over time, including baseline, ranged between 20 ml/100g/min and 80 ml/100g/min with means that did not differ statistically from baseline flows. However, microcirculation values for each subject and tissue region were reduced from baseline, although their confidence intervals crossing the horizontal ratio of 1 indicated that such reduction was not statistically significant. Histological analysis demonstrated the presence of moderate and severe score on the amyloid staining throughout both hemispheres. Conclusions: Microcirculation at the ipsilateral and contralateral site of a contusion and the ipsilateral thalamus and medulla showed a consistent decline over time. Our data suggests that after severe head injury, microcirculation in pre-defined areas of the brain is reduced from baseline with amyloid staining in those areas reflecting the early establishment of axonal injury.